2022
DOI: 10.3390/ijms232112875
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer with Increased Drug Resistance, Invasion Ability, and Cancer Stem Cell Properties through Metabolism Reprogramming

Abstract: Breast cancer is a heterogeneous disease, and the survival rate of patients with breast cancer strongly depends on their stage and clinicopathological features. Chemoradiation therapy is commonly employed to improve the survivability of patients with advanced breast cancer. However, the treatment process is often accompanied by the development of drug resistance, which eventually leads to treatment failure. Metabolism reprogramming has been recognized as a mechanism of breast cancer resistance. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…The researchers found that these changes were associated with alterations in the expression of genes involved in glucose, lipid, and amino acid metabolism. These findings suggest that metabolic reprogramming may be a key factor in the development of drug resistance and metastasis in breast cancer 20 …”
Section: Breast Cancer and Its Classificationmentioning
confidence: 85%
See 1 more Smart Citation
“…The researchers found that these changes were associated with alterations in the expression of genes involved in glucose, lipid, and amino acid metabolism. These findings suggest that metabolic reprogramming may be a key factor in the development of drug resistance and metastasis in breast cancer 20 …”
Section: Breast Cancer and Its Classificationmentioning
confidence: 85%
“…These findings suggest that metabolic reprogramming may be a key factor in the development of drug resistance and metastasis in breast cancer. 20 Gene expression-based profiling by Kay et al resulted in breast cancer cell line classification into four major subtypes: luminal A, luminal B, basal-like, and claudin-low. 21 A study of DNA methylation patterns revealed a distinct subtype of breast cancer called HER2-positive/low basal that is characterized by high levels of DNA methylation.…”
Section: Breast Cancer and Its Classificationmentioning
confidence: 99%
“…Consistent with the results obtained from the in vitro cell culture, BB-Cla combined with Doc has an obviously additive inhibitory effect against the expression of CD133 and SOX2 in tumour tissues (figure 3 b and electronic supplementary material, S2 b ). Of note, the invasive ability of tumour cells is closely related to the characteristics of tumour stemness [51,52]. We continued to detect the changes of the cell invasive ability upon drug treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Metabolism reprogramming has also been recognized as a mechanism of breast cancer resistance. The metabolic profiles showed that there were 25 metabolites with significant changes, including 4 exhibited decreased levels and 21 exhibited increased levels, in doxorubicin-resistant MCF-7 cells [40]. Min et al reported that the level of G6PD (glucose-6-phosphate dehydrogenase) and metabolites of 3-phosphoglycerate and ribulose-5-phosphate production were both increased in paclitaxel-resistant cells [41].…”
Section: Discussionmentioning
confidence: 99%